Glutamate supplementation, endocrine profile, and ovarian activity interaction in crossbreed goats during the seasonal anestrous - Luna García, Luis Antonio (Universidad Autónoma Chapingo, 2025)
Seasonal reproduction in goats requires the integration of internal and external signals to regulate the reproductive axis. These seasonal changes affect production in the axis, resulting in a discontinuous pattern that negatively impacts the profits and yields of goat producers. In mammals, glutamate plays a key role in modulating key neuroendocrine and reproductive processes. To evaluate its possible effect on the metabolic and reproductive performance during the seasonal anestrus, two experiments (Exp. 1 & Exp. 2) were conducted using yearling goats (n = 20), divided into two experimental groups: (1) GLUT; n = 10; live weight (LW) = 29.1 ± 1.02 kg; body condition score (BCS) = 3.4 ± 0.2, and (2) CONT; n = 10; LW = 29.2 ± 1.07 kg; BCS = 3.5 ± 0.2. In Exp. 1, the secretion pattern of luteinizing hormone (LH) and the total ovarian activity (TOA) defined as the sum of antral follicles (AF) and ovulation rate (OR), were evaluated. In Exp. 2, serum insulin levels and TOA were analyzed. In the Exp. 1, the GLUT group showed a higher (p<0.05) number of LH pulses (5.0 vs. 2.2 pulses/6 h) and an augmented (p<0.05) TOA as compared to the CONT group. Besides, in Exp. 2, the GLUT group exhibited increases (p<0.01) in both serum insulin levels and TOA during regarding to the CONT group. These findings support glutamate supplementation as a promising strategy to mitigate the effects of reproductive seasonality in small ruminants, improving both reproductive and metabolic parameters during the non reproductive season.
Tesis (Doctorado en Ciencias en Recursos Naturales y Medio Ambiente en Zonas Áridas)
Keywords: Goats, glutamate, seasonal anestrous, ovarian activity